Model of Teaching Malay Language to Non-Native and Foreign Speaker - Janan, Dahlia; Mohamad Tarmizi, Mohd Hafiz; Setyosari, Punaji; Jamaluddin, Norliza; Abu Bakar, Siti Saniah; Lin, Chia Ying (Universiti Utara Malaysia Press, 2024)
Purpose – This study aims to develop a teaching model of the Malay language for non-native and foreign speakers in schools. Implementing this model can assist educators in teaching the Malay language to students who do not use it as their first language in everyday use.